Climate change, groundwater and the law: exploring the connections in South Africa. Issue 6 (18th August 2017) - Kidd, Michael
ABSTRACT: Projected impacts of climate change on water availability in South Africa are likely to result in the increasing use of groundwater, which is relatively underused at present. Several threats to groundwater, including acid mine drainage, pervasive water pollution (particularly from untreated sewage), and planned hydraulic fracturing will have to be addressed to protect the country's groundwater reserves. This article considers the role that law can play in both managing groundwater and protecting it from these and other threats.